A theoretically informed, mixed-methods study of pharmacists’ aspirations and readiness to implement pharmacist prescribing - Derek Stewart (117849) (2022)
Background Studies have highlighted advancing clinical pharmacy practice in Qatar. Objective To explore pharmacists’ aspirations and readiness to implement pharmacist prescribing. Setting Hamad Medical Corporation (HMC), the main provider of secondary and tertiary care. Method A sequential explanatory mixed-methods design. Questionnaire items were derived from the Consolidated Framework of Implementation Research (CFIR), in domains of: awareness/support; readiness; implementation; and facilitators and barriers. Following piloting, all pharmacists (n = 554) were invited to participate. Questionnaire data were analysed using descriptive and inferential statistics with principal component analysis of attitudinal items. Focus groups were recorded, transcribed and analysed using the Framework Approach. Main outcome measure Aspirations and readiness to implement pharmacist prescribing. Results The response rate was 62.8% (n = 348), with respondents highly supportive of implementation in Qatar (median 4, scale 0–5, extremely supportive). The majority (64.9%, n = 226) considered themselves ready, particularly those more senior (p < 0.05) and classifying themselves innovative (p < 0.01). Outpatient (72.9%, n = 221 agreeing) and inpatient (71.1%, n = 218 agreeing) HMC settings were those perceived as being most ready. PCA identified 2 components, with ‘personal attributes’ being more positive than ‘prescribing support’. Facilitators were access to records, organizational/management support and the practice environment, with physician resistance and scope of practice as barriers. Focus groups provided explanation, with themes in CFIR domains of innovation characteristics, characteristics of individuals and the inner setting. Conclusion HMC pharmacists largely aspire, and consider themselves ready, to be prescribers with inpatient and outpatient settings most ready. CFIR domains and constructs identified as facilitators and barriers should be focus for implementation. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11096-021-01296-1